2020
DOI: 10.1186/s13765-020-00561-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferation effect of sulforaphene isolated from radish (Raphanus sativus L.) seeds on A549 cells

Abstract: Sulforaphene (SFE), a major isothiocyanate in radish seeds, is a close chemical relative of sulforaphane (SFA) isolated from broccoli seeds and florets. The anti-proliferative mechanisms of SFA against cancer cells have been well investigated, but little is known about the potential anti-proliferative effects of SFE. In this study, we showed that SFE purified from radish seeds inhibited the growth of six cancer cell lines (A549, CHO, HeLa, Hepa1c1c7, HT-29, and LnCaP), with relative half maximal inhibitory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Among the health-promoting biomolecules mentioned before, GSLs stand out due to their antifungal, antibacterial, antioxidant, antimutagenic, hepatoprotective, nephroprotective, antidiabetic, anti-inflammatory, and antiproliferative activities. , These sulfur-rich anionic secondary metabolites are classified into three groups based on their amino acid precursors: aliphatic, aromatic, and indolic GSLs . GSLs usually undergo a process of degradation by the myrosinase enzyme (EC 3.2.1.147), giving the bioactive molecules isothiocyanates (ITCs) .…”
Section: Introductionmentioning
confidence: 99%
“…Among the health-promoting biomolecules mentioned before, GSLs stand out due to their antifungal, antibacterial, antioxidant, antimutagenic, hepatoprotective, nephroprotective, antidiabetic, anti-inflammatory, and antiproliferative activities. , These sulfur-rich anionic secondary metabolites are classified into three groups based on their amino acid precursors: aliphatic, aromatic, and indolic GSLs . GSLs usually undergo a process of degradation by the myrosinase enzyme (EC 3.2.1.147), giving the bioactive molecules isothiocyanates (ITCs) .…”
Section: Introductionmentioning
confidence: 99%
“…Radish seeds contain health-promoting compounds such as sulforaphene and glucosinolates, which are found in cruciferous vegetables ( Gutiérrez and Perez, 2004 ). Sulforaphene is a bioactive compound with anticancer effects that induces cell apoptosis and which has a similar chemical structure to sulforaphane isolated from broccoli seeds ( Lim et al, 2020 ). Glucosinolates are organic compounds that are known for their powerful antimicrobial and anticancer properties.…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer effects on human breast cancer cells, human lung cancer cells, human hepatocarcinoma cells, and human oesophageal cancer cells have been previously reported. [51][52][53][54][55] In addition, anti-adipogenic effects on mouse adipocytes and anti-neuroinflammatory effects in model rats with Alzheimer's disease have been described. 56,57 The present study showed that the hepatoprotective effect of sulforaphene was nearly equal to that of sulforaphane and the amount of sulforaphene in daikon radish sprouts was higher than that of sulforaphane in broccoli sprouts.…”
Section: Papermentioning
confidence: 99%